PROBLEMATICS OF CERTAINTY OF WORK PERIOD OF GOVERNMENT EMPLOYEES WITH CONTRACT AGREEMENTS (PPPK) HUMAN RIGHTS PERSPECTIVE - Sihombing, Eka NAM; Abdillah Sihombing, Muhammad Aufa (NOMOI Law Review, 2024)
Government employees with contract agreements or often known as PPPK have been around for quite a long time. PPPK has even provided its own dynamics related to the personnel management system in Indonesia. PPPK can be said to be a transformation and eliminates the terminology of honorary employees. The PPPK nomenclature has actually existed since the birth of Law No. 5 of 2014 concerning the State Civil Apparatus. However, Law No. 20 of 2023 concerning the State Civil Apparatus provides more strengthening of the rights of PPPK. In both laws, PPPK is placed as part of the state civil apparatus (ASN) just like civil servants. However, even though it is included in ASN, the rights obtained by PPPK are not the same as PNS. Even PPPK using a contract system certainly does not provide certainty about its work period. This study uses normative legal research with the approach used being the statutory approach. The results of the study show that the existence of PPPK since 2014/2015 has been known. In 2023, since the birth of Law No. 20 of 2023 concerning State Civil Apparatus, the rights obtained by PPPK are stronger. However, regarding the certainty of the work period, PPPK still has differences with PNS. The work period of PNS will end when they reach retirement age, while PPPK will end their work period when the work agreement period ends. So that PPPK can be extended again or not based on the needs of each agency and an assessment of the achievement of performance targets which causes there to be no certainty regarding the work period for employees with PPPK status.